A study of number marking in Izere nouns - Adewumi Anthony Erin (Journal of Modern Languages)
This research descriptively examines number marking in Izere nouns, using morpholexical rules as proposed by Lieber (1980).  In essence, it describes noun inflections for number from base forms in Izere, with the aid of these rules. Data for the research were collected in Fobur, Jos East Local Government Area of Plateau State, using selected nouns from the Ibadan wordlist of 400 basic items, alongside an adapted list of nouns specifically designed for the research. The selected nouns were collected electronically and then transcribed in a way that identified the inflected noun forms from the base ones. The data were then analyzed qualitatively. Morpholexical rules were also proposed to account for morphological changes in the inflected forms of these nouns. The research findings indicate that affixation, tone pattern change and suppletion are the dominant morphological processes that account for noun inflections for number in Izere.